2012
DOI: 10.1096/fj.11-201822
|View full text |Cite
|
Sign up to set email alerts
|

A novel stroke therapy of pharmacologically induced hypothermia after focal cerebral ischemia in mice

Abstract: Compelling evidence from preclinical and clinical studies has shown that mild to moderate hypothermia is neuroprotective against ischemic stroke. Clinical applications of hypothermia therapy, however, have been hindered by current methods of physical cooling, which is generally inefficient and impractical in clinical situations. In this report, we demonstrate the potential of pharmacologically induced hypothermia (PIH) by the novel neurotensin receptor 1 (NTR1) agonist ABS-201 in a focal ischemic model of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 68 publications
5
127
0
Order By: Relevance
“…For infarct volume measurement, animals were sacrificed 24 hours after transplantation and their brains were removed and placed in a coronal brain matrix. Brains were sliced into 1-mm-thick sections, and infarct volume was determined using 2,3,5-triphenyltetrazolium chloride staining as detailed in [27].…”
Section: Stroke Model Cell Transplantation and Measurement Of Cell mentioning
confidence: 99%
“…For infarct volume measurement, animals were sacrificed 24 hours after transplantation and their brains were removed and placed in a coronal brain matrix. Brains were sliced into 1-mm-thick sections, and infarct volume was determined using 2,3,5-triphenyltetrazolium chloride staining as detailed in [27].…”
Section: Stroke Model Cell Transplantation and Measurement Of Cell mentioning
confidence: 99%
“…As for the function of autophagy in I/R, a growing body of evidence indicates that autophagy, triggered by ischemia may, leads cells to death, especially in the brain [84][85][86][87][88]. However, this depend on cell type and duration of I/R as there are a great number of studies shown autophagy works to keep cells safe from death [89].…”
Section: Autophagy and Ischemia/ Reperfusionmentioning
confidence: 99%
“…Compelling evidence suggests neuroprotective effects of neurotensin (8-13) analogs against acute ischemic stroke [12,72,73]. ICV injection of JMV-449, a pseudopeptide analogue of neurotensin (8-13), quickly induced hypothermia and decreased infarct size in mice after MCAO [72].…”
Section: Neurotensin (Nt) Systemmentioning
confidence: 99%
“…ICV injection of JMV-449, a pseudopeptide analogue of neurotensin (8-13), quickly induced hypothermia and decreased infarct size in mice after MCAO [72]. ABS-201 lowered core body temperature by 2-5°C in 15-30 min and maintained body temperature below 35°C for six hours in mice [12]. ABS-201was able to decrease infarct size by 30-40% and to improve long-term neurological function [12].…”
Section: Neurotensin (Nt) Systemmentioning
confidence: 99%
See 1 more Smart Citation